Science Learning Through Realia and Manipulative Media: An Application of Bandura’s Social Learning Theory - Rey Mar Engcong; Nicole Andrea Botes; Marielle Cordova; Elayza Rae Lara; Rey Melitante; Haya Jane Elan (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study explored how realia and manipulative media contribute to students' perceived learning in science, particularly in terms of knowledge retention anchored in Albert Bandura’s Social Learning Theory that investigates how these instructional materials are utilized to gain a deeper understanding of students’ learning experiences and perceptions. Methodology: A phenomenological qualitative research design was used to scrutinize the experiences of eight Grade 10 learners from the St. Pius X section, Holy Trinity College of General Santos City, Philippines. Data were gathered through semi-structured interviews, audio-recorded, transcribed, and analyzed thematically. The interview protocol and ethical guidelines were taken into consideration to ensure the study's trustworthiness. Main Findings: The use of realia and manipulative media enhances learners’ ability to visualize scientific processes, improves memory retention, and increases engagement and interest in lessons. However, challenges such as limited access to materials and lack of guidance were noted as barriers to full participation and effective learning. The findings significantly emphasize the importance of thoughtfully integrating realia and manipulative media into science instruction to promote meaningful, relevant, and responsive learning experiences. Novelty/Originality of this study: The educational benefits of tangible materials are well-documented quantitatively; a critical gap in understanding the lived experiences of learners navigating these tools remains unexplored while explicitly framed within the retention component of Bandura’s Social Learning Theory. Through providing adequate empirical evidence, this study offers paramount insights by capturing the nuanced, firsthand perspectives of students as they socially construct scientific knowledge.